Logistic regression analysis in Bronchopulmonary Dysplasia - 238494 Kavitha Samannamuthaliar (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Sains (Matematik Industri)) - Universiti Teknologi Malaysia, 2008